Passing the Talking Stick: Resilience-Making through Storytelling. Issue 2 (1st June 2020) - Unknown
Abstract : Young Indigenous Women's Utopia . 2019. Treaty 6 Traditional Homeland of the Metis People (Saskatoon, SK): Self-published with support from York University, McGill University, and Networks for Change and Well-being: Girl-led 'from the ground up' Policy Making to Address Sexual Violence in Canada and South Africa. To order a copy email yiwutopia@gmail.com